Pengaruh Pengetahuan Ibu Terhadap Status Gizi Balita - Arief, Ria Qadariah; Hidayati L, Sri; Prasetyaningtyas, Linda Widayanti (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
The nutritional status of toddlers is a crucial point to see their growth and development in the future. To support this growth and development, nutritional knowledge is needed which can have the greatest influence in assisting the lives of these toddlers. This study aims to analyze the relationship between mothers' knowledge about nutrition and the nutritional status of their toddlers. The research used a cross-sectional study to see this relationship by measuring mothers' knowledge about nutrition by means of knowledge scoring, measuring the nutritional status of toddlers with weight based on age and height based on age which is chronic nutritional status. The result is that maternal knowledge has a significant impact on the nutritional status of toddlers. Therefore, it is important to increase mothers' knowledge, especially regarding health and nutrition.